Internationalizing German Communication Studies: Learning From the World. A Conversation Between Carola Richter, Anna Litvinenko, Subekti Priyadharma and Hanan Badr (Global Media Journal - German Edition, 2024)
The following debate was set up as a roundtable during the conference “Internationalizing German Communication Studies: Learning from the World” in Erfurt, Germany, in March 2024. It features three scholars originally from Russia, Indonesia and Egypt, who have been socialized both in their native and the German communication studies community and thus can refer to both “worlds” in terms of a critical analysis, but also regarding academic best practices for a deep internationalization in communication studies. The debate aims to share their (subjective) experiences and to gather ideas of what could be improved and what should be continued regarding a cosmopolitization of study programs, university structures, and research foci in German communication studies institutes.
Keywords: Kommunikationswissenschaftliche Studiengänge; Epistemologie; Wissensproduktion; Russland; Indonesien; Ägypten; Globaler Süden; akademische Zusammenarbeit; Wissenschaftsfreiheit